Variáveis intervenientes da resposta cognitiva de pacientes com doença de Alzheimer submetidos à neuromodulação associada a intervenção cognitiva - Fonsêca, Égina Karoline Gonçalves da (2020)
Alzheimer's disease (AD) is the neurodegenerative pathology with the highest incidence. Its diagnosis is eminently clinical and occurs after the discovery of deficits in two or more cognitive processes, promoting a functional impact on the individual. AD has no cure and pharmacological treatment is only intended to delay the symptoms associated with the progression of the case. Therefore, the need for studies to assess the effectiveness of nonpharmacological alternatives for its treatment. In this context, Transcranial Direct Current Stimulation (TDCS) and Cognitive Intervention (CI) stand out, which have shown good results when applied together. However, there are still few replicated results that guarantee the clinical efficacy of this treatment and many studies have heterogeneous responses. Thus, the objective of this work was to evaluate the influence of intervening variables on the cognitive response in patients with AD, in the initial phase, undergoing TDCS associated with CI. Patients were randomly allocated to 4 groups that received different interventions: 1- active TDCS + active CI; 2- sham TDCS + active CI; 3- active TDCS + sham CI; 4- sham TDCS + sham CI. The individuals were evaluated, underwent 2 months of neurostimulation, with 3 sessions per week, and at the end, they were reassessed to verify the possible cognitive gains. Due to the sample size, it was not possible to visualize, with statistically significant data, the clinical effect of the therapies. The results showed no difference between groups, so there was no improvement. However, among the variables pointed out as possible predictors of the clinical response, the presence of white substance hypodensity, presented a strong negative correlation with the mean changes in the patients' scores. Suggesting that the higher the level of white matter, the less chance of improvement of patients undergoing the clinical trial. It is concluded that it is important to carry out more studies that evaluate structural and functional changes in the pathological brain of AD and how much they can result in qualitatively different responses to brain stimulation, to elucidate the real mechanisms of TDCS, especially when used together.